Characterization of Activated Carbon Fibre Derived from Palm Empty Fruit Bunch Waste and Cassava Stem for Urea Adsorption - Amran, Nasuha; Nasrul Fikry Che Pa (Progress in Engineering Application and Technology, 2021)
The study of activated carbon fiber derived from agricultural waste has bring a lot of attention to researchers all around the world. Activated carbon fibers generated from cassava stem and empty fruit bunch waste have a high propensity to serve as a dispersing agent where chemical and physical treatments may change the activated carbon surface. The characteristics of activated carbon which is highly porous, has large surface area make it suitable to be used in many applications in the chemical, pharmaceutical and food industries. Hence, the objective of this study is therefore to determine the effectiveness of empty fruit bunch waste and cassava stem from last decades in derivation to activated carbon fibre. The best chemical agent between acidic and basic also were studied. Thus, the basic which is KOH frequently used by many researchers compared to the other chemical agents as it has been found to be effective in activated carbon production with a narrow pore size distribution and well-developed porosity. This study also revealed that physical and chemical properties of activated carbon fibre (adsorption capacity, pore volume, and carbon yield) affected by parameters such as microwave radiation time, the microwave power level, the impregnation ratio and the agent flow rate. In general, the physical properties of activated carbon fibre improved when these parameters were enhanced up to their optimum points and then the properties decreased when these parameters increased beyond their optimum values. In short, the chemical agents and the parameters were important in producing activated carbon fibre derived from agricultural waste.